AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAN FRAKSI KULIT BATANG BELIMBING WULUH (Averrhoa bilimbi Linn.) TERHADAP BAKTERI Klebsiella pneumoniae DAN Staphylococcus epidermidis BESERTA BIOAUTOGRAFINYA - , MSi., Dr. Muhtadi; Ambarwati, Ria; Yuliani, Ratna (Biomedika, 2012)
Belimbing wuluh (Averrhoa bilimbi Linn.) is a tropical plant that has antibacterial properties. The purpose of this study was to test the antibacterial activity of bark Belimbing wuluh against Klebsiella pneumoniae and Staphylococcus epidermidis and their bioautography. Extraction methods used to research is method maceration with a solvent ethanol 96 %. Fractinations done by method partition liquid-liquid with a separating funnel. Test performed in this research covering identi cation bacteria, the sensitivity bacteria, antibacterial activity, thin layer chromatography, bioautography. The result of antibacterial activity ethanol extract of disk diffusion method with concentrations 400 μg/disk, 800 μg/disk, 1600 μg/disk is 8±0,5; 10,34±0,58; 12,17±0,76 on Klebsiella pneumoniae, 10,17±0,29; 11±0; 11.5±0 on Staphylococcus epidermidis, n-hexane fraction with concentration 400 μg/disk, 800 μg/disk, 1600 μg/disk is 8,34±0,29; 9,34±0,29; 10,84±0,76 on Klebsialla pneumoniae, 8,5±0,5; 9,34±0,29; 10,67±0,29 on Staphylococcus epidermidis, ethyl acetate fraction with concentration 400 μg/disk, 800 μg/disk, 1600 μg/disk is 9,17±0,29; 10,34±0,29; 11,17±0,29 on Klebsiella pneumoniae and 9,5±0,5; 10,67±0,29; 12,67±1,26 on Staphylococcus epidermidis, ethanol-water fractions with concentration 400 μg/disk, 800 μg/ disk, 1600 μg/disk is 8,17±0,29; 9,17±0,29; 10±0 on Klebsiella pneumoniae, 9±0; 9,67±0,29; 10,34±0,29 on Staphylococcus epidermidis. The TLC show chemical compounds contained in the ethanol extract, n-heksan fraction, ethyl acetate fraction, and ethanol-water fraction is a compound of the saponins, alkaloids, avonoids and phenolic. Bioautography showed that ethanol extracts, n-heksan faction, ethyl acetate fraction, and etanol-airfaction Belimbing wuluh (Averrhoa bilimbi Linn.) bark have not antibacterial activity because there is no clear area around on plate TLC.Keywords: Belimbing wuluh (Averrhoa bilimbi Linn.), ethanol extract, fractination, antibacterial, bioautogra .